1987
DOI: 10.1152/jappl.1987.63.5.2067
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation during sleep onset

Abstract: There is now considerable evidence which indicates that respiratory activity is different during sleep compared with wakefulness. However, there has been little work on respiratory changes during the transitional period from wakefulness to sleep. The present study was concerned with the quantitative and temporal properties of ventilation during sleep onset. Sleep onsets were studied in five young male adults in a series of single-subject designs in which sleep onsets were replications. The results indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 79 publications
(209 reference statements)
3
36
0
Order By: Relevance
“…There are also physiologic changes in respiration. While there may be more rhythmic respirations during onset of sleep, there is also a relative fall in abdominal respiration compared to thoracic, a decrease in tidal volume, an increase in pCO 2 , a decrease in ventilatory responsiveness to hypercapnia and hypoxia, and an increase in airflow resistance (Colrain et al, 1987;Colrain et al, 1990;Naifeh and Kamiya, 1981;Ogilvie and Wilkinson, 1984;Trinder et al, 1992). The rhythmic deeper respiration during the sleep onset period produces the expected increase in heart rate variability measures secondary to sinus arrhythmia.…”
Section: Physiological Changes Other Than Eegmentioning
confidence: 99%
“…There are also physiologic changes in respiration. While there may be more rhythmic respirations during onset of sleep, there is also a relative fall in abdominal respiration compared to thoracic, a decrease in tidal volume, an increase in pCO 2 , a decrease in ventilatory responsiveness to hypercapnia and hypoxia, and an increase in airflow resistance (Colrain et al, 1987;Colrain et al, 1990;Naifeh and Kamiya, 1981;Ogilvie and Wilkinson, 1984;Trinder et al, 1992). The rhythmic deeper respiration during the sleep onset period produces the expected increase in heart rate variability measures secondary to sinus arrhythmia.…”
Section: Physiological Changes Other Than Eegmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Inspiratory breathing sounds can vary significantly across sleep and between subjects; in some cases the sounds may be soft (sound intensity < 40 dB), but in others it can be loud. [8][9][10][11][12][13][14][15][16] Intense breathing sounds are commonly referred to as snoring.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that this period is associated with marked changes in a host of physiological and behavioral phenomena, as well as in subjective experience (Ogilvie & Wilkinson, 1984). Physiological phenomena associated with sleep onset include: decrease in high frequency electroencephalographic (EEG) activities (e.g., Azekawa, Sei, & Morita, 1990;Davis, Davis, Loomis, Harvey, & Hobart, 1937, 1938Hori, 1985;Merica, Fortune, & Gaillard, 1991;Rechtschaffen & Kales, 1968;Tsuno et al, 2002); the absence and presence of different event-related potential (ERP) components (for review, see Campbell, Bell, & Bastien, 1992;Harsh, Voss, Hull, Schrepfer, & Badia, 1994); the appearance of slow eye movements (e.g., De Gennaro, Ferrara, Ferlazzo, & Bertini, 2000;Porte, 2004); the absence of elicited skin conductance responses (e.g., Johnson, 1970); a drop in the core body temperature and an increase in the distal skin temperature (e.g., Barrett, Lack, & Morris, 1993;Krauchi, Cajochen, Werth, & Wirz-Justice, 2000;Wehr, 1990); and, substantial, rapid reduction in respiration (e.g., Colrain, Trinder, Fraser, & Wilson, 1987;Naifeh & Kamiya, 1981). Behavioral indicators of sleep onset include: a decrease in sensory threshold, a cessation of responses to external stimuli (e.g., Anliker, 1966;Ogilvie & Simons, 1992;Ogilvie, Simons, Kuderian, MacDonald, & Rustenburg, 1991;Ogilvie & Wilkinson, 1984, 1988Ogilvie, Wilkinson, & Allison, 1989;Simon & Emmons, 1956), and a decrease in muscle strength (e.g., Jacobson, Kales, Lehmann, & Hoedemaker, 1964;Litchman, 1974) were also observed in the course of the sleep onset process.…”
Section: Introductionmentioning
confidence: 99%